Unpublished Economic Texts From the Old Babylonian Period - Hussain, Shaimaa Nassir (Al-Adab Journal, 2019)
The cuneiform texts considered one of the most important resources which play an important role , and help us to know how was the economic , politic and religious conditions , and everything related of the history of Mesopotamia , which contain many information that enrich our knowldgement about Mesopotamia civilization , since using writing as a way to documentation the science and human knowldgement .